Caracterização funcional do produto da ORF NCU03043 de Neurospora crassa homólogo ao fator de transcrição FlbC de Aspergillus nidulans - Boni, Ana Carolina [UNESP] (2014)
The filamentous fungus Neurospora crassa is a model organism widely used for studies of several aspects of the biology in eukaryotes. We have been studying the molecular and biochemical mechanisms involved in glycogen metabolism regulation in this fungus. The screening of a knocked-out strains set in genes encoding transcription factors has identified many proteins likely involved in the regulation of glycogen metabolism in the fungus N. crassa. Among the proteins, the transcription factor FLBC was identified as a regulatory protein of the glycogen metabolism. The mutant strain showed changes in the glycogen accumulated and in the gsn gene expression when compared to the wild-type strain under heat stress. Preliminary studies carried out in our laboratory showed severe morphological changes in the strain flbCKO, such as reduced ability to conidiate, presence of a few microconidia, reduced production of aerial hyphae, altered morphology of hyphae tips, changes in the colonies morphology and high production of the pigment melanin, suggesting that FLBC plays an important role in the fungus development. The transcription factor FLBC, object of study in this work, is the Aspergillus nidulans and Podospora anserina FlbC/FLE1 homologous protein, respectively, both involved in conidiation and fungal growth. The purpose of this study was to perform functional characterization of this transcription factor in N. crassa. Analysis of gene expression showed high levels of the transcript flbC during vegetative growth and after induction of asexual development. The knockout strain presented a misregulation in the accumulation of reserve carbohydrate (glycogen and trehalose) during vegetative growth accumulating higher levels of both carbohydrates as compared to the wildtype strain. Analysis of gene expression in the strains wild-type and flbCKO showed that gdn (encoding for debranching enzyme) and gpn (encoding glycogen phosphorylase) genes are...